Estrategias pedagógicas para detectar la dislexia en el aula de clase de los niños y niñas de 5-6 años de la sede cañasgordas de incolballet de Cali - Panchalo Torres, María Andrea (Educación, 2016)
The research project: teaching to detect cases of dyslexia in children of 5-6 years the seat Incolballet fat rods Cali posed as children through teaching strategies are linked strategies in education in which they find it understandable that way is greatly improved academic performance in children and their active participation against activities. Teachers gain an insight into the teaching strategies that should be implemented to identify dyslexic children. They take into account disturbing demonstrations by children and will support them so that they unfold within and outside the classroom to enable children with dyslexia detected before sending it to a specialist.